Sildenafil Prevents Endothelial Dysfunction Induced by Ischemia and Reperfusion via Opening of Adenosine Triphosphate–Sensitive Potassium Channels: A Human In Vivo Study - Gori, Tommaso; Sicuro, Silvia; Dragoni, Saverio; Donati, Giovanni; Forconi, Sandro; Parker, John D. (Circulation (New York, N.Y.), 2005)
Background— Animal studies have demonstrated that administration of sildenafil can limit myocardial damage induced by prolonged ischemia, an effect that appears to be mediated by opening of adenosine triphosphate–sensitive potassium (K ATP ) channels. No study has investigated whether sildenafil can also prevent the impairment in endothelium-dependent vasodilatation induced by ischemia-reperfusion (IR) in humans. Methods and Results— In a double-blind, placebo-controlled, crossover design, 10 healthy male volunteers (25 to 45 years old) were randomized to oral sildenafil (50 mg) or placebo. Two hours later, endothelium-dependent, flow-mediated dilatation (FMD) of the radial artery was measured before and after IR (15 minutes of ischemia at the level of the brachial artery followed by 15 minutes of reperfusion). Seven days later, subjects received the other treatment (ie, placebo or sildenafil) and underwent the same protocol. Pre-IR radial artery diameter and FMD, as well as baseline radial artery diameter after IR, were similar between visits ( P =NS). After placebo administration, IR significantly blunted FMD (before IR: 7.9±1.1%; after IR: 1.2±0.7%, P <0.01). Importantly, sildenafil limited this impairment in endothelium-dependent vasodilatation (before IR: 7.0±0.9%; after IR: 6.2±1.1%, P =NS; P <0.01 compared with placebo). In a separate protocol, this protective effect was completely prevented by previous administration of the sulfonylurea glibenclamide (glyburide, 5 mg), a blocker of K ATP channels (n=7; FMD before IR: 10.3±1.5%; after IR: 1.3±1.4%, P <0.05). Conclusions— In humans, oral sildenafil induces potent protection against IR-induced endothelial dysfunction through opening of K ATP channels. Further studies are needed to test the potential clinical implications of this finding.